“The Triumph of Vegetation is Total”: a Re-Reading of Michel Houellebecq’s La carte et le territoire from the Perspective of the Environmental Humanities - Sommerfeld, Beate (Porównania, 2021)
The article deals with the interdependences between humans and their natural environment as developed in Houellebecq’s The Map and the Territory (2010). These are negotiated via the visual arts. The paintings and photographs by the artist Jed Martin reflect the place of humans in nature and culture, thereby shifting the agency from humans to nature. The last photographic installations adopt the perspective of vegetation, which has replaced human agency. Through the medium of art, Houellebecq’s novel creates transversal alliances, practices and visions that are at odds with the industrial-technological hybris of the Anthropocene. Houellebecq’s text is reflected in the context of the ethical debate about the Anthropocene.